2017
DOI: 10.3390/f8060177
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress Reaction of Growth and Δ13C in Tree Rings of European Beech and Norway Spruce in Monospecific Versus Mixed Stands Along a Precipitation Gradient

Abstract: Tree rings include retrospective information about the relationship between climate and growth, making it possible to predict growth reaction under changing climate. Previous studies examined species-specific reactions under different environmental conditions from the perspective of tree ring growth and 13 C discrimination (∆ 13 C). This approach is extended to monospecific versus mixed stands in the present paper. We investigated the resistance and resilience of Norway spruce (Picea abies [L.] Karst) and Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 57 publications
4
22
0
Order By: Relevance
“…The frequency and duration of drought periods are expected to increase in spring and summer in boreal conditions like elsewhere, especially under severe climate warming [24]. This may make the growing conditions sub-optimal, especially for Norway spruce and partially also for Scots pine, and more optimal for broadleaves (see e.g., [2,4,12,20,52,53]), which need to be considered when adapting management to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency and duration of drought periods are expected to increase in spring and summer in boreal conditions like elsewhere, especially under severe climate warming [24]. This may make the growing conditions sub-optimal, especially for Norway spruce and partially also for Scots pine, and more optimal for broadleaves (see e.g., [2,4,12,20,52,53]), which need to be considered when adapting management to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of a changing climate, close-to-nature (CTN) forestry can contribute to increasing the resiliency of forest stands to natural disturbances such as pests, pathogens, windthrows, and drougths (Schütz et al 2006, Morrison et al 2014, Felton et al 2016, Schäfer et al 2017. The popularity of CTN and continuouscover forestry has been on the rise in German public forests and in several other European countries.…”
Section: Introductionmentioning
confidence: 99%
“…The severe climate warming and associated increase in drought events may make the current growing conditions suboptimal for some tree species and more optimal for others (see e.g., Kellomäki et al 2008Kellomäki et al , 2018Allen et al 2010;Lindner et al 2010Lindner et al , 2014Kolström et al 2011;Granda et al 2013;Taeger et al 2013;Schäfer et al 2017). Currently, the growing conditions in southern Finland are near optimum, especially for Norway spruce (Picea abies (L.) Karst.…”
Section: Impacts Of Forest Management and Climate Change On Finnish Fmentioning
confidence: 99%
“…Moreover, Henttonen et al (2015) found that the growth of Scots pine in Finland might also decrease under climate change, even at high northern latitudes. Additionally, in central Europe, especially Norway spruce will most likely suffer especially under changing climate (e.g., Hanewinckel et al 2013;Schäfer et al 2017).…”
Section: Effects Of Climate Change Projections On Volume Growth Carbmentioning
confidence: 99%